Crystal structures of β‐1, 4‐N‐acetylglucosaminyltransferase 2: structural basis for inherited muscular dystrophies. Issue 4 (7th April 2021) - Yang, Jeong Yeh; Halmo, Stephanie M.; Praissman, Jeremy; Chapla, Digantkumar; Singh, Danish; Wells, Lance; Moremen, Kelley W.; Lanzilotta, William N.
Abstract : Crystal structures of human β‐1, 4‐ N ‐acetylglucosaminyltransferase 2, an enzyme essential for O ‐mannosylation, are reported, revealing a novel domain organization and providing the first rational basis for an explanation of the loss‐of‐function mutations observed in the clinic. Abstract : The canonical O ‐mannosylation pathway in humans is essential for the functional glycosylation of α‐dystroglycan. Disruption of this post‐translational modification pathway leads to congenital muscular dystrophies. The first committed step in the construction of a functional matriglycan structure involves the post‐translational modification of α‐dystroglycan. This is essential for binding extracellular matrix proteins and arenaviruses, and is catalyzed by β‐1, 4‐ N ‐acetylglucosaminyltransferase 2 (POMGNT2). While another glycosyl transferase, β‐1, 4‐ N ‐acetylglucosaminyltransferase 1 (POMGNT1), has been shown to be promiscuous in extending O ‐mannosylated sites, POMGNT2 has been shown to display significant primary amino‐acid selectivity near the site of O ‐mannosylation. Moreover, several single point mutations in POMGNT2 have been identified in patients with assorted dystroglycanopathies such as Walker–Warburg syndrome and limb girdle muscular dystrophy. To gain insight into POMGNT2 function in humans, the enzyme was expressed as a soluble, secreted fusion protein by transient infection of HEK293 suspension cultures. Here, crystal structures of POMGNT2 (amino‐acid residues 25–580) with and without UDP bound are reported. Consistent with a novel fold and a unique domain organization, no molecular‐replacement model was available and phases were obtained through crystallization of a selenomethionine variant of the enzyme in the same space group. Tetragonal (space group P 421 2; unit‐cell parameters a  =  b  = 129.8, c  = 81.6 Å, α = γ = β = 90°) crystals with UDP bound diffracted to 1.98 Å resolution and contained a single monomer in the asymmetric unit. Orthorhombic (space group P 21 21 21 ; unit‐cell parameters a = 142.3, b  = 153.9, c  = 187.4 Å, α = γ = β = 90°) crystals were also obtained; they diffracted to 2.57 Å resolution and contained four monomers with differential glycosylation patterns and conformations. These structures provide the first rational basis for an explanation of the loss‐of‐function mutations and offer significant insights into the mechanics of this important human enzyme.